KEBIJAKAN CONGRESSMAN MOONEY SEBAGAI STRATEGI MENGHADAPI KEKUATAN BRICS - Rahmi Fitriyanti; Azhar Fuad Nugraha; Nina Amalia; Rafi Baron Juliaqil (Penerbit Media Wawasan Ilmu, 2022)
The initiation of returning to the gold standard in the United States economy has been carried out by Congressman Alexander Mooney who represents West Virginia. The Bills intend to define the fixed exchange rates of the dollar as the total weight of gold in a country. The concept of theory Neo-Classical Realism was used to lead to the various aspects of background both internal and external to study the establishment of the bills. Congressman Mooney believed that the bills will be a solution to deal with inflationary conditions, the growth of national debt, and the instability of the ongoing monetary system. However, the bills seem to be also an affirmation from the United States in the international economy and maybe hamper the rise of the BRICS organization which currently gathering its strength in the world.